ChatGPT, Python, and Microsoft Excel - Kaique Sbampato; Humberto Arruda; Édison Renato Silva (Journal of the Medical Library Association)
This article examines how the integration of ChatGPT, Python, and Microsoft Excel can significantly enhance the productivity of medical librarians. These tools provide a powerful framework for automating tasks, processing large datasets, and generating actionable insights. ChatGPT, with its advanced natural language processing, helps automate Python script generation and improve data processing in Excel, streamlining workflows and enabling more precise service delivery. Practical applications demonstrate improvements in information retrieval, data management, and research support. The results show that, despite some integration challenges, these technologies have the potential to greatly elevate the efficiency and effectiveness of librarians in managing healthcare data.